Defining incident radiographic hip osteoarthritis for epidemiologic studies in women. - Arden, N; Lane, N; Parimi, N; Javaid, K; Lui, L; Hochberg, M; Nevitt, M (2009)
OBJECTIVE: To evaluate definitions of radiographic hip osteoarthritis (RHOA) for use in longitudinal epidemiologic studies of disease incidence in women. METHODS: We studied 5,839 women from the Study of Osteoporotic Fractures who had had serial pelvic radiographs obtained (mean of 8.3 years apart) and who were followed up (mean followup 7.1 years from the time of the second radiograph) for evaluation of clinical outcomes. Definitions of RHOA were assessed for construct validity (association with symptoms and signs at the time of the second radiograph) and predictive validity (association with total hip replacement [THR] and signs and symptoms a mean of 7.1 years later). Odds ratios (ORs) and 95% confidence intervals were calculated to assess the strength of association using logistic regression. RESULTS: The cumulative incidence of RHOA ranged from 2.2% to 11.7%. All definitions displayed significant construct validity; the most consistent was found for composite definitions that required the concurrent presence of 2 or more individual radiographic features and definitions based on stringent criteria for joint space narrowing. All definitions except minimum joint space < or =2.5 mm displayed consistent predictive validity. Composite definitions had the strongest associations with THR (OR 10.5-18.5) and hip pain (OR 2.6-2.9). The hips identified as having OA by each definition varied, with especially small overlap between findings using definitions based on osteophytes and those using definitions based on joint space narrowing alone. CONCLUSION: Most definitions of incident RHOA display good construct and predictive validity. Composite definitions have the best overall performance, and definitions requiring the presence of both osteophytes (in particular, femoral osteophytes) and joint space narrowing would be recommended for most epidemiologic and genetic studies.